From WhatsApp to Whiteboard: Intra-Cultural Norms and EFL Interaction in Indonesian MTs Classrooms - Dian Fera Pratiwi; Syarifuddin Dollah; Nur Ima (Universitas Islam Negeri Palopo, 2025)
This mixed-methods study investigates how intra-cultural norms shape English as a Foreign Language (EFL) interaction among Grade IX students in an Indonesian Islamic junior high school. Data were collected from 40 students and two English teachers over two months through classroom observations, a 12-item questionnaire, and interviews. Quantitative findings show high levels of intra-cultural awareness, with no significant gender differences, and a moderate positive correlation between intra-cultural awareness and students’ digital participation. Qualitative analysis using Braun and Clarke’s thematic approach identified four overarching themes illustrating how cultural values guided participation, humor use, peer correction, and teacher mediation in both classroom and WhatsApp-based interaction. Overall, the study demonstrates that intra-cultural norms operate as both supportive and restrictive forces in students’ communicative behavior across face-to-face and digital settings. The findings highlight the importance of culturally responsive EFL pedagogy and suggest integrating socio-pragmatic awareness into instructional practices to better align English learning with students’ local communicative realities.